Genetic variability, correlation and path analysis of exotic and local hybrid maize (Zea mays L.) genotypes - Ahmed, Nlima; Chowdhury, Abul Kashem; Uddin, Md Saleh; Rashad, Md Mainul Islam (Asian Journal of Medical and Biological Research, 2020)
The genetic parameters, characters association and path coefficient analysis between yield and yield components of 32 exotic and local hybrid maize genotypes were studied at Plant Breeding division, Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Rahmatpur, Barisahl during rabi 2015 to 2016, following Alpha Lattice Design with three replications. All the characters showed significant differences among the genotypes except cob length indicating their wide genetic variation. The highest genotypic co-efficient of variation (11.48) observed in yield and lowest (1.72) was found in days to maturity. All of the characters exhibited moderate to high heritability in broad sense (h2b) coupled with a wide range of genetic advance and genetic advance in percentage of mean. Heritability ranged from 19.21 to 86.79 for cob length and thousand seed weight, respectively. Yield had a significant positive correlation with cob length, cob diameter, number of seeds per cob and number of rows per cob. Days to tasseling and number of seeds per cob make highest positive contribution toward yield. While, days to silking and ear height had highest negative direct effect on yield. The results indicated that ear height, number of rows per cob, thousand seeds weight and number of seeds per cob could be considered as selection criteria in maize breeding program. Asian J. Med. Biol. Res. March 2020, 6(1): 8-15